The Unemployment Dilemma of University Graduates: Bridging the Skills Gap in the Labor Market—Evidence from Afghanistan - Abdul Rahman Adeli; Sayed Masood Habibi (Demagogi: Journal of Social Sciences, Economics and Education, 2026)
Graduate unemployment emerges as a pressing global challenge in higher education and labor market dynamics, acutely intensified in fragile economies like Afghanistan, where prolonged economic instability and structural shifts have widened skills mismatches. Recent years have witnessed a disconnect between educational outputs and market absorption, resulting in youth unemployment rates around 16.7% in 2024, with educated graduates facing disproportionate barriers to productive employment. This study investigates the skills gap as the primary mediator of graduate unemployment in Afghanistan, emphasizing deficiencies in practical competencies, digital literacy, and entrepreneurial skills amid theoretical curricula and systemic resource constraints. The research adopts a mixed-methods approach, integrating secondary analysis of international reports with qualitative insights from existing faculty and graduate perceptions. Key findings reveal that mismatches stem largely from outdated programs and limited industry alignment, perpetuating informal employment and brain drain. Recent studies underscore the critical need to align technical and vocational curricula with labor market needs to foster economic growth. Furthermore, the role of universities in empowering individuals is pivotal, yet current institutional capacities are strained by economic limitations. These patterns amplify economic fragility, constraining productivity and growth. Theoretically, the study extends human capital and skills mismatch frameworks to conflict-affected contexts, proposing a fragility-integrated model incorporating economic and structural moderators. Policy implications advocate curriculum modernization toward competency-based learning and international support for TVET and private-sector linkages to enhance employability. Bridging this gap is essential for harnessing Afghanistan's youthful demographic dividend and fostering sustainable recovery, underscoring the necessity of robust research to guide these reforms.